Are mycorrhizal fungi our sustainable saviours? Considerations for achieving food security. (July 2017) - Thirkell, Thomas J.; Charters, Michael D.; Elliott, Ashleigh J.; Sait, Steven M.; Field, Katie J.
Summary: The 20th century saw dramatic increases in agricultural productivity, largely through the development and application of pesticides, fertilisers rich in nitrogen and phosphorus, and advances in plant breeding and genetic technologies. In the last 15 years, however, many key crop yields have plateaued. Climate change, an ever‐increasing human population, depletion of global rock‐phosphorus and growing energy prices make current fertiliser production unsustainable and represent sizeable challenges to global food security. Many important crops form symbioses with arbuscular mycorrhizal fungi (AMF), and this has motivated the development of novel approaches in crop breeding and agricultural practices to support and promote AMF in agroecosystems. Arbuscular mycorrhizal fungal symbiosis can be high beneficial in crops and wider agroecosystems in many ways, including improved soil structure and resistance to pests. However, AMF colonisation does not necessarily translate directly into enhanced plant performance or crop yield, while land management practices that would encourage mycorrhiza–crop associations, such as low‐till or minimal chemical input often incur yield‐reducing trade‐offs. Synthesis . We draw on ecological knowledge of AMF to inform their role in agroecosystems, providing a balanced look at mycorrhiza–crop symbioses in terms of plant ecophysiology and the wider role of AMF in agroecosystems and ask the question: are AMF our sustainable saviours? Abstract : In this mini‐review, we draw on ecological and physiological knowledge of arbuscular mycorrhizal fungi to inform their role in agroecosystems, providing a balanced look at mycorrhiza–crop symbioses in terms of plant ecophysiology and the wider role of mycorrhizas in agroecosystems, asking the question: are mycorrhizal fungi our sustainable saviours?